An Inulin-Enriched Soy Drink and Its Lowering Effect on Oxidized Low Density Lipoproteins in Healthy Volunteers - Liutkevičius Algirdas; Speičienė Vilma; Vaičiulytė-Funk Lina; Mieželienė Aldona; Alenčikienė Gitana; Abaravičius Algis; Bagdonaitė Loreta; Jablonskienė Valerija; Kaminskas Arvydas (Polish Journal of Food and Nutrition Sciences)
Due to selection of appropriate ingredients and parameters, a microbiologically-safe drink enriched with soy protein isolate (SPI) and prebiotic dietary fiber inulin with high scores of acceptability was produced. The results of medical nutrition survey showed that on the 21 day of using drink the level of oxidized low density lipoproteins (LDL) significantly decreased while the other biochemical parameters of blood of healthy patients as compared to the control tests remained unchanged. As well there was no apparent impact on the intestinal microflora balance of recipients established.